Pengaruh Model Discovery Learning Berbantuan Media Ular Tangga Berbasis Genially terhadap Kemampuan Membaca Pemahaman Peserta Didik Kelas IV SDN 28 Cakranegara - Ernawati; Husniati; Heri Setiawan (Mataram University, 2026)
This study aims to determine the effect of the Discovery Learning model assisted by Genially-based snakes and ladders media on the reading comprehension ability of fourth-grade students at SDN 28 Cakranegara. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The research sample consisted of 60 students, including 30 students in the experimental class and 30 students in the control class. Data collection techniques included tests and observations. The data were analyzed using descriptive statistics and inferential statistics through normality tests, homogeneity tests, and Independent Sample t-tests. The results showed that the average Post-Test score of the experimental class was 70.83, which was higher than the control class score of 68.00. In addition, the hypothesis testing result obtained a significance value (2-tailed) of 0.004 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The effect size calculation using Cohen’s d formula obtained a value of 0.19, which was categorized as a small effect. Therefore, it can be concluded that the Discovery Learning model assisted by Genially-based snakes and ladders media had an effect on students’ reading comprehension ability.